The Bone Morphogenetic Protein Pathway: The Osteoclastic Perspective - Lademann, Franziska; Hofbauer, Lorenz C.; Rauner, Martina (Frontiers in Cell and Developmental Biology, 2020)
Bone health crucially relies on constant bone remodeling and bone regeneration, both tightly controlled processes requiring bone formation and bone resorption. Plenty of evidence identifies bone morphogenetic proteins (BMP) as major players in osteoblast differentiation and thus, bone formation. However, in recent past years, researchers also increasingly reported on the pivotal role of these multi-functional growth factors in osteoclast formation and activity. This review aims to summarize the current knowledge of BMP signaling within the osteoclast lineage, its role in bone resorption, and osteoblast-osteoclast coupling. Furthermore, subsequent clinical implications for recombinant BMP therapy will be discussed in view of recent preclinical and clinical studies.